INITIAL ROASTING TEMPERATURE EFFECT ON THERMAL BEHAVIOUR AND CHARACTERISTIC OF LIBERICA COFFEE - Heriyanti, Heriyanti; Panggabean, Yulia; Pangestu, Enggar Tyas; Asyhar, Rayandra; Sutrisno, Sutrisno (Coffee Science - ISSN 1984-3909, 2019)
The roasting process has brought about some changes in transition phases, in chemical characteristics, and microstructures of minerals in the Liberica coffee beans. Two initial roasting temperature variations were carried out to study the thermal behavior and characteristic of Liberica coffee, namely 200 °C and 230 °C. The thermal behaviour of phase changes of the Liberica green and ground coffee after the roasting process has been identified by using Differential Scanning Calorimeter (DSC). Chemical functional groups and molecular structures have been well-analyzed by using Fourier-Transform Infrared Spectroscopy (FTIR), Liquid Chromatography-Mass Spectrometry (LC-MS), Scanning Electron Microscope with Energy Dispersive X-Ray Spectroscopy (SEM/EDX) and X-Ray Powder Diffractions (XRD) for the green and roasted Liberica coffee. The DSC spectra indicated a high decomposition process that occurred during thermal treatment with crystallization and melting temperature around 120 °C and 325 °C for both roasting initial temperature variations, respectively. The FTIR and LC-MS are able to identify the chemical change in both the green and the roasted coffee. The dominant compounds found in the roasted Liberica coffee are caffeine, trigonelline, nicotinic acid, and dehydrocafestol. The XRD spectrum indicates that there is an amorphous phase for the green coffee and a sucrose crystal phase for the roasted coffee within the activity in 2θ = 20.3° and 21.1°.